DESARROLLOS HIPERMEDIALES DEL GRUPO LINGUATICs - González, Henry; Vera, Esperanza (Tecné, Episteme y Didaxis: TED, 2002)
This paper aims at socializing the two research projects proposed by the group LINGUATICs from Universidad Pedagógica Nacional, made up by 10 teachers from different content areas and 3 students, all belonging to the Language Department. The project “Hypermedia for the Development of Literature Didactics based On the short; short story HIMINI” seeks to integrate two apparently dissimilar disciplines, such as information Technology and Literature, in order to develop a new proposal regarding Literature Didactics; it is based on the most representative verbal literary work nowadays, that is, the short, short story The project “ Design and Validation of a Hypermedia for the English Learning”, seeks lo produce an interactive hypermedia game which can be sensitive to the difficulties the user can find when using it, so as lo pro vide him with information or training on effective strategies lo process information heard and interact with the characters, based on it.